(untitled) (Journal of Management, 2023)
This article attempts to take up again the four-year compulsory English syllabus of Bachelor of Business Studies (BBS) introduced to the first phase in 2013 AD. It also aims at looking into the basic differences between the English syllabus of 2013 AD and the present syllabus which was launched by Tribhuvan University in 2019 AD. In the course of dealing with the issue, the article intended to avail the descriptive design in which the two periods’ syllabuses were set one against another and explained in terms of English Language Teaching (ELT) pedagogy, utility, and appropriateness to the context of learners’ lives. The comparative study of these courses revealed that the earlier course was more appropriate than the latter one. More specifically, the earlier course was designed to teach language through literature, and the topics were selected with the clear aims of facilitating the learners for the best socialization, friendship, and conjugal life. This article could be helpful for students, teachers, course book compilers, and course designers.